Effects of Rutin on Wound Healing in Hyperglycemic Rats - Li-You Chen; Chien-Ning Huang; Chih-Kai Liao; Hung-Ming Chang; Yu-Hsiang Kuan; To-Jung Tseng; Kai-Jung Yen; Kai-Lin Yang; Hsing-Chun Lin (MDPI AG, 2020)
Long-term poor glycemic control negatively affects macrovascular and microvascular diseases, as well as wound restoration. Buckwheat is a good source of rutin (quercetin-3-O-rutoside) and has benefits in regulating blood sugar. This study was to evaluate the antioxidant and anti-inflammatory effects of rutin on wound healing in streptozotocin-induced hyperglycemic rats. Eighteen male Wistar rats were randomly divided into three groups: normal (NDM), hyperglycemic (DM), and hyperglycemic with rutin (DMR). After induction of hyperglycemia for 2 days, a 15 × 15 mm wound was induced on the back of each rat. Intraperitoneal injection of rutin significantly ameliorated diabetes-induced body weight loss and improved metabolic dysfunctions of hyperglycemic rats. Based on appearance and histopathological staining, rutin promotes wound healing and inhibits production of inflammatory cells. The immunoblotting data indicated that rutin promotes production of antioxidant enzymes induced by nuclear factor erythroid 2-related factor 2 (NRF2), inhibits the expression of matrix metalloproteinases (MMPs) regulated by NF-κB, and decreases the expression of vascular endothelial growth factor (VEGF). It also promotes the expression of neurogenic-related protein (UCH-L1). The aforementioned results indicated that rutin reduces oxidative stress and inflammatory response in hyperglycemic rats, promoting wound healing and subsequently reducing the risk of wound ulcers.